"Fixing" the Journalist-Fixer Relationship: A Critical Look Towards Developing Best Practices in Global Reporting. (10th September 2019) - Plaut, Shayna; Klein, Peter
ABSTRACT: Sociologists and media scholars have offered a robust body of literature regarding the daily workings of global journalism – both in newsrooms and with freelancers. Within this literature, which is both critical and reflexive, the role of fixers is acknowledged, but rarely questioned. Such work often fails to critically examine power dynamics inherent in the actual institutional and global arrangement. This project aims to fill this gap, focusing on the realities and constraints of editorial agency by fixers. Through a large-scale survey (450 responses from more than 70 countries) followed by 35 semi-structured interviews with journalists, fixers and people who identify as both, we map current trends and highlight nuanced dynamics and tensions within the practice. Specifically, we sought to understand what effect, if any, the fixer has in shaping the content of a story, highlighting the disjuncture between journalists and fixers in recognizing the potential editorial impacts. Lastly, the work examines the inequality between international journalists and their local fixers worldwide, and seeks to examine how the relationship is understood culturally within the rapidly changing field of global journalism. This article not only identifies problems within current practices, but also explores potential remedies.